Letter (copy) : Delegation on situation in Spain - Citrine, Walter, 1887-1983
1936-12-14 WMC/EAB/AC/247 International 14th December, 1936. Mr. Leon Jouhaux, Confederation Generale du Travail, 211, rue Lafayette, PARIS, Xe. Dear Comrade Jouhaux, DELEGATION ON SITUATION IN SPAIN. With reference to the delegation consisting of Messrs. Longuet, Morizet, Langevin, Basch and Belin, which recently visited London with a view to strengthening opposition to the Non-Intervention Agreement, you will probably be aware that, so far as the British Labour Movement is concerned, it is felt necessary to ensure that all contacts and approaches regarding international action are of an official character, pursued in cooperation with the L.S.I, and the I.F.T.U. In view of this, the National Council of Labour, which is representative of the Trades Union Congress, Labour Party and Parliamentary Labour Party, disapprove of individual delegations, or the circularising of them as individual members of the Internationals, and in order to preserve that coordination of international policy and the loyalty to the two Internationals, which the National Council of Labour feel sure you will agree to be desirable and indispensable, they do not feel that delegations carrying no direct representative credentials should be encouraged. This does not mean of course that any expression of opinion between National Centres should be curtailed, 292/946/10/32(i)